Impact of absorptive capacity and ambidexterity on innovation - Del Carpio Gallegos, Javier Fernando (2021)
This study attempts to design an approach showing how absorptive capacity and ambidexterity are related to technological innovation in Peruvian manufacturing firms. A structural equation model is proposed. The sample is made up of 783 manufacturing firms. It was found that although Peruvian manufacturing firms invest little money in research and development, they are capable of developing dynamic capabilities, such as absorptive capacity and ambidexterity in order to better carry out technological innovation.